Constraints from C-O-Sr isotopes on the origin of carbonate minerals in coal-bearing sequences from the Dong Open-pit Mine, Ningwu coal field, Shanxi, China - Shaobo Di; Shifeng Dai; Baruch Spiro; Antonio Delgado; David French; Ian Graham; Jingjing Liu; Shaowei Zhang (Journal of Asian Earth Sciences, 2026)

Hydrothermal alterations of the Ordovician carbonate reservoir rocks in the Ordos Basin - Nana Mu; Wenhui Huang; Bo Jiu; Baruch Spiro (Marine and Petroleum Geology, 2025)

Multi-stage hydrothermal activity affecting the early Jurassic K7 coal seam from the Gaosheng coal Mine, Sichuan Basin, southwest China: Evidence from whole-rock geochemistry and C-O-Sr isotopes in authigenic carbonates - Rongjie Wang; Shifeng Dai; Baruch F. Spiro; Victor P. Nechaev; David French; Ian T. Graham; Mingxuan Zhou; Jingjing Liu; Shaobo Di; Xiao Tian (Journal of Asian Earth Sciences, 2025)

Net primary productivity of paleo-peatlands linked to deep-time glacial periods in the late Carboniferous and early Permian icehouse interval - Yanwen Shao; Fenghua Zhao; Baruch Spiro; Dehui Li; Guangyuan Mu; Jiangman Chu; Jing Lu; Longyi Shao (International Journal of Coal Geology, 2024)

Geochemical and mineralogical evidence for the formation of siderite in Late Permian coal-bearing strata from western Guizhou, SW China - Minglian Shen; Shifeng Dai; David French; Ian T. Graham; Baruch F. Spiro; Na Wang; Xiao Tian (Chemical Geology, 2023)

Hydrothermally-altered coal from the Daqingshan Coalfield, Inner Mongolia, northern China: Evidence from stable isotopes of C within organic matter and C-O-Sr in associated carbonates - Qian Wang; Shifeng Dai; David French; Baruch Spiro; Ian Graham; Jingjing Liu (International Journal of Coal Geology, 2023)

Distribution of Li, Ga, Nb, and REEs in coal as determined by LA-ICP-MS imaging: A case study from Jungar coalfield, Ordos Basin, China - Bo Jiu; Wenhui Huang; Baruch Spiro; Ruilin Hao; Nana Mu; Long Wen; Huidi Hao (International Journal of Coal Geology, 2023)

Mineralogical, chemical and stable C and O isotope characteristics of surficial carbonate structures from the Mediterranean offshore Israel indicate microbial and thermogenic methane origin - Baruch Spiro; Oded Ezra; Jens Najorka; Antonio Delgado; Or Bialik; Zvi Ben-Avraham; Dwight Coleman; Yizhaq Makovsky (Geo-Marine Letters, 2021)
The Eastern Mediterranean continental slope offshore Israel became a focus of exploration for, and production of, natural gas in recent years. The 2010–2011 Nautilus ROV expedition performed detailed video recordings and sampling in two areas offshore Israel: the Palmachim disturbance, southwest of Tel Aviv, and an area offshore Acre, north of Haifa. An analytical programme regarding the carbonate structures was carried out, examining the overall mineralogy, stable C and O isotopes, and Ca, Mg, and Mn concentrations. This provided information on their composition and as a result, an indication of the carbon sources and temperature of formation. The major authigenic minerals identified comprised magnesian calcite, dolomite, aragonite, and kutnohorite. The detrital minerals included quartz, clays, feldspars, and rare augite and enstatite, likely transported from the Nile estuary. The carbon isotope composition of aliquots taken from nineteen samples from these areas have an overall δ 13 C range from −62.0 to −0.1‰PDB, indicating a range of microbial/biogenic and thermogenic methane contributions. The range of δ 18 O from 2.7 to 7.0‰PDB reflects the range of temperatures of formation. The δ 18 O characteristics differ among areas. In general, high values; δ 18 O >5‰PDB are recorded from area N2 of the Palmachim disturbance, indicating low temperature of formation. Low values of δ 18 O (<5‰PDB) were measured from areas W2 and W3 of the Palmachim disturbance, together with samples from area N2 of the Palmachim disturbance, and samples from areas A1 and A2 offshore Acre indicate high temperature origin. Samples from an inactive chimney from area N2 range from pure dolomite to pure magnesian calcite. This trend is linked to δ 13 C increase from −39.9 to −0.1‰(PDB), and δ 18 O decrease from 6.2 to 4.7‰(PDB). These values indicate a decrease in the methane-derived carbon contribution and an increase in temperature. Kutnohorite, Ca(Mn 2+ , Mg, Fe 2+ )(CO 3 ) 2 is a major component in samples from Acre, and less so in the Palmachim disturbance. An exploratory investigation of the relationship between Mn/Ca, δ 18 O and δ 13 C revealed that samples having Mn/Ca < 0.1(wt./wt.) have δ 13 C<−50‰PDB indicating a microbial methane source, while samples with Mn/Ca > 0.1 have δ 13 C between −35 and −22‰PDB suggesting a thermogenic origin. These results suggest that the mineralogical, isotopic δ 13 , δ 18 O, and chemical (Mn/Ca indicative of kutnohorite) characteristics of surficial carbonate structures can indicate and distinguish between deep and shallow methane sources in the Eastern Mediterranean.

Deducing the source and composition of rare earth mineralising fluids in carbonatites: insights from isotopic (C, O, 87Sr/86Sr) data from Kangankunde, Malawi - Sam Broom-Fendley; Frances Wall; Baruch Spiro; Clemens V. Ullmann (Contributions to Mineralogy and Petrology, 2017)

Lacustrine sediments and lichen transplants: two contrasting and complimentary environmental archives of natural and anthropogenic lead in the South Urals, Russia - Baruch Spiro; Valery Udachin; Ben J. Williamson; O. William Purvis; Svetlana G. Tessalina; Dominik J. Weiss (Aquatic Sciences, 2013)

Rapid microbial stabilization of unconsolidated sediment against wind erosion and dust generation - Javier Cuadros; Baruch Spiro; William Dubbin; Premroy Jadubansa (Journal of Soils and Sediments, 2010)

Trends in 13C/12C ratios and C isotope discrimination of wheat since 1845 - Fang-Jie Zhao; Baruch Spiro; Steve P. McGrath (Oecologia, 2001)

Potential canopy influences on the isotopic composition of nitrogen and sulphur in atmospheric deposition - T. H. E. Heaton; Baruch Spiro; S. Madeline C. Robertson (Oecologia, 1997)